Potensi Rumput Laut (Eucheuma cottonii J.Agardh) Terhadap Nefropati Diabetik Tikus Putih Jantan (Rattus norvegicus): (Potency of Seaweed (Eucheuma cottonii J.Agardh) Against Nephropathy Diabetic Male White Rats (Rattus norvegicus)) - Tandi, Joni; Dewi, Niluh Puspita; Wirawan, Resky Chandra; Surat, Megawati R. (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
ABSTRACT This study aims to determine the effect of a multilevel dose of ethanol extract of seaweed (Eucheuma cottonii J. Agardh) on the decreasing blood glucose levels and kidney tissue regeneration of hypercholesterolemia-diabetic male white rats. 24 rats were divided into 6 groups, namely groups 1-3 (normal control, negative control, and positive control/Glibenclamide, respectively) and groups 3-6 (seaweed extract doses of 100, 200, and 400 mg/kg BW per oral, respectively). Rats were induced by high fat diet and Streptozotocin. Histopathological picture of the kidney was observed by HE staining using 400 magnifications. Data scoring of the level of kidney damage were analyzed by One Way ANOVA at a 95% confidence level and a Least Significant Difference (LSD) test was conducted. Seaweed ethanol extract at a dose of 100 mg/kg BW was effective in reducing blood glucose levels with an average value of 122.25 mg/dL and effective in regenerating the kidney tissue of male white rats with an average value of damage of 1.9. Therefore, seaweed extract has potency to be developed and further investigated as an antidiabetic agent.